Harnessing AI to cultivate curiosity in history learning as a tool to combat extreme poverty - Lee, Bih Ni; Christina Andin; Connie Shin @ Connie Cassy Ompok (RSIS International, 2025)
This study explores how artificial intelligence (AI) can be harnessed to cultivate curiosity in history learning as a strategic tool to combat extreme poverty. By synthesizing primary data, quantitative metrics, and qualitative insights, the research reveals that AI-driven educational technologies personalize historical content, stimulate inquiry-based learning, and foster deeper student engagement particularly in under-resourced settings. Evidence from field studies and international reports indicates that AI not only enhances cognitive development and historical thinking but also improves educational outcomes in marginalized communities. The findings suggest that fostering curiosity through AI-supported history education can empower learners with critical awareness and knowledge, contributing to poverty alleviation by promoting long-term educational equity and opportunity.